#TITLE_ALTERNATIVE# - NOVIANTRI (NIM 20107005), VISKA
In this final project we study the relevance of sinusoidal bed as beach protection. Here, we take into account the presence of current and hard wall beach on the right. We apply the multiple scale asymptotic expansion method to the linear Shallow Water Equation for sinusoidal beds with current. Bragg resonance will occur if the wavelength of the wave is twice the wavelength of sinusoidal bed. When there is current, there are two wave numbers that lead to Bragg resonance, while there is only one wave number in no current case. A relatively small amplitude of sinusoidal beds can reduce the amplitude of incoming waves effectively, due to Bragg resonance. The situation will be different when there is a hard wall beach on the right. The presence of sinusoidal bed will increase the wave amplitude that hit the beach much higher, and hence increase the hazard to the beach. The situations will less severe if the beach can absorb the wave partially.